2011
DOI: 10.1073/pnas.1104619108
|View full text |Cite
|
Sign up to set email alerts
|

Composite scaffold provides a cell delivery platform for cardiovascular repair

Abstract: Control over cell engraftment, survival, and function remains critical for heart repair. We have established a tissue engineering platform for the delivery of human mesenchymal progenitor cells (MPCs) by a fully biological composite scaffold. Specifically, we developed a method for complete decellularization of human myocardium that leaves intact most elements of the extracellular matrix, as well as the underlying mechanical properties. A cellmatrix composite was constructed by applying fibrin hydrogel with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
204
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(210 citation statements)
references
References 50 publications
4
204
1
1
Order By: Relevance
“…The created scaffolds fulfill both of these criteria: The elastic modulus of 15–132 kPa displayed by the scaffolds under tension fits well into the range measured for cardiac muscle 20–500 kPa,24 and resides within the interval (7.9–1200 kPa) that has been reported in previous cardiac biomaterial studies 25, 26, 27, 28, 29, 30…”
Section: Discussionsupporting
confidence: 83%
“…The created scaffolds fulfill both of these criteria: The elastic modulus of 15–132 kPa displayed by the scaffolds under tension fits well into the range measured for cardiac muscle 20–500 kPa,24 and resides within the interval (7.9–1200 kPa) that has been reported in previous cardiac biomaterial studies 25, 26, 27, 28, 29, 30…”
Section: Discussionsupporting
confidence: 83%
“…44 It is not clear at this point how the reported formation of new myocardium is compatible with the extremely low capacity of the adult mammalian heart to regenerate cardiac myocytes. 45 Most studies to date concluded that the reported beneficial effects of injecting alginate, 46 ECM, 47 or nanofibers 48 into infarcted hearts are likely independent of the formation of new heart muscle and potentially because of improved angiogenesis or mechanical stabilization of the ventricular wall. Similar mechanisms have been suggested to account for the beneficial effects of cell therapy.…”
Section: Heart Tissue For Cardiac Regeneration Different Approaches Amentioning
confidence: 99%
“…An elaborated approach was developed by Godier-Furnémont et al 47 Scaffolds were made from decellularized human hearts, seeded with mesenchymal stem cell in a fibrin hydrogel, and implanted onto infarcted nude rat hearts. This promoted an arteriogenic response and improved functional recovery, particularly when mesenchymal stem cells had been in vitro preconditioned by transforming growth factor-β before cell seeding.…”
Section: Hirt Et Al Cardiac Tissue Engineering 359mentioning
confidence: 99%
“…Many recent studies have shown that decellularized tissues provide an excellent matrix for the differentiation of mesenchymal stem cells into the original tissue type. 54,55 Thus, the combination of different matrices appears to have a major effect on the differentiation process. It will be important to use a variety of different matrix ligands to determine how the synergy of different integrin binding components occurs.…”
Section: Synergy In Activation Of Integrin Clustersmentioning
confidence: 99%